Insider Trading in Emerging Countries: Prevalence, Challenges, and Policy Implications - Dote-Pardo, Jairo; Severino-González, Pedro (European Public & Social Innovation Review, 2025)
Introduction: This study explores insider trading in emerging markets, examining its regulatory, economic, and behavioural aspects. Its objective is to understand the implications for market efficiency, corporate governance, and policymaking. Methodology: A multi-method approach combines bibliometric analysis, systematic review, and content analysis of articles indexed in Web of Science and Scopus. Results: The results show a notable increase in research on insider trading in emerging markets, especially after 2015. Journals indexed in Web of Science lead both in publication volume and citation impact. Key research topics include regulatory challenges, governance deficiencies, cultural and behavioural influences, and the connection between insider trading and overall market dynamics. Discussions: The study highlights the importance of robust legal frameworks, effective governance, and context-adapted enforcement. It also highlights the growing relevance of technologies such as AI and blockchain to improve transparency and foster investor confidence. Conclusions: This research addresses a need by providing an integrated bibliometric and thematic assessment of insider trading in emerging markets.